Formulasi Hybrid Contract Sebagai Alternatif Pembiayaan Pertanian Di Bank Syariah - Pratiwi, Rahmi; Noprizal, Noprizal (Sekolah Tinggi Agama Islam Negeri Curup, 2017)
This research uses interpretive approach. This approach is chosen to understand a symptom both oral and written, and aims to know a symptom of the symptoms themselves are studied in depth using the instrument interview or interview with informants. This research was conducted to understand how the portrait of agricultural financing in both Islamic banks namely Bank Muamalat and BPRS SAFIR Curup branch. The results showed that the existing agricultural financing in both sharia banks using murabaha schemes used to finance the goods or tools that support the agricultural business. According to the authors, murabahah contract is not appropriately applied to the agricultural sector because it has not been able to answer the needs of farmers. A more precise contract is profit-sharing such as muzaraah or mukhabarah. Therefore, the authors recommend the formulation of contracts on the agriculture sector based on hybrid contracts namely bai al-wafa wal muzaraah and bai al-wafa wal mukhabarah.